Patterns of resource use in loggerhead turtle (Caretta caretta) from the Southwestern Atlantic Ocean - Celina Carolina Almeida; Rodrigo F. Bastos; Sérgio C. Estima; Andrine Paiva da Silva; Gabriela M. Vélez-Rubio; Danielle S. Monteiro (Marine Biology, 2026)
The Southwestern Atlantic Ocean (SWAO) is an important feeding and developmental area for loggerhead turtle ( Caretta caretta ). However, long-term patterns of resource use across life stages and sexes remain poorly understood for the species in this region. Here, we used stable isotope analysis (SIA) of sequential layers of carapace scutes to investigate resource use of loggerhead turtles in the SWAO across life stages and sexes. Scute samples were collected from 42 individuals stranded or incidentally caught by pelagic longline and bottom pair trawl fishery in southern Brazil and Uruguay (from 31º21′S–51º05′W to 34º55′S–56º09′W), between 2013 and 2024. Cluster analysis based on δ¹⁵N values revealed two distinct groups, corresponding to oceanic and neritic foraging habitats, whereas linear mixed models indicated ontogenetic increases in δ¹³C and δ¹⁵N values consistent with habitat shifts. Significant differences between sexes were observed only for δ¹³C values. Bayesian mixing models (MixSIAR) were used to estimate prey contributions to the diet, based on isotopic values from the literature, revealing a dominance of pelagic prey in oceanic non-shifters and of benthic invertebrates in neritic non-shifters. Shifters showed a transition from oceanic to neritic habitats, with a dietary shift from pelagic to benthic prey, reflecting two main ontogenetic shift patterns: discrete and facultative. Our results enhance the understanding of life-history variation in loggerhead turtles and highlight that sequential analysis of carapace scutes is a valuable tool for reconstructing long-term resource use patterns, providing a broader view of the ecology of this long-lived and endangered species.